Drug Transport Mechanism of Oral Antidiabetic Nanomedicines - Gundogdu, Evren (Kowsar, 2014)
CONTEXT: Over the last few decades, extensive efforts have been made worldwide to develop nanomedicine delivery systems, especially via oral route for antidiabetic drugs. Absorption of insulin is hindered by epithelial cells of gastrointestinal tract, acidic gastric pH and digestive enzymes. EVIDENCE ACQUISITION: Recent reports have identified and explained the beneficial role of several structural molecules like mucoadhesive polymers (polyacrylic acid, sodium alginate, chitosan) and other copolymers for the efficient transport and release of insulin to its receptors. RESULTS: Insulin nanomedicines based on alginate-dextran sulfate core with a chitosan-polyethylene glycol-albumin shell reduced glycaemia in a dose dependent manner. Orally available exendin-4 formulations exerted their effects in a time dependent manner. Insulin nanoparticles formed by using alginate and dextran sulfate nucleating around calcium and binding to poloxamer, stabilized by chitosan, and subsequently coated with albumin showed a threefold increase of the hypoglycemic effect in comparison to free insulin in animal models. Solid lipid nanoparticles showed an enhancement of the bioavailability of repaglinide (RG) within optimized solid lipid nanoparticle formulations when compared with RG alone. CONCLUSIONS: Nanoparticles represent multiparticulate delivery systems designed to obtain prolonged or controlled drug delivery and to improve bioavailability as well as stability. Nanoparticles can also offer advantages like limiting fluctuations within therapeutic range, reducing side effects, protecting drugs from degradation, decreasing dosing frequency, and improving patient compliance and convenience